2010
DOI: 10.1002/ejoc.200901286
|View full text |Cite
|
Sign up to set email alerts
|

Horner–Wadsworth–Emmons Reaction of Unprotected Sugars in Water or in the Absence of Any Solvent: One‐Step Access to C‐Glycoside Amphiphiles

Abstract: The synthesis of C‐glycosides in water or in the absence of any solvent from free sugars and β‐keto phosphonates is reported. The methodology permits a one‐step access to C‐glycoside amphiphiles in moderate‐to‐good yields. The selectivity (α/β and furanoside/pyranoside) is discussed and a process that leads to pure β‐C‐pyranosides is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…In cases where enones or enaldehydes are produced in the olefination reaction, a 1,4-addition becomes a possibility; this includes the Michael addition [149][150][151]. Also, the combination of ring opening of cyclic hemiacetals or acetals, olefination reaction and a 1,4-addition leading to ring closure is quite common [154][155][156]. The outcome of one-pot sequences of olefination reaction-electrocyclic rearrangement can be predicted less easily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where enones or enaldehydes are produced in the olefination reaction, a 1,4-addition becomes a possibility; this includes the Michael addition [149][150][151]. Also, the combination of ring opening of cyclic hemiacetals or acetals, olefination reaction and a 1,4-addition leading to ring closure is quite common [154][155][156]. The outcome of one-pot sequences of olefination reaction-electrocyclic rearrangement can be predicted less easily.…”
Section: Resultsmentioning
confidence: 99%
“…In their synthesis to C-glycoside amphiphiles, Ranoux et al followed a similar strategy, reacting non-protected sugars with HWE reagents in aqueous or solventless conditions, leading to C-glucosides 117 and 121 (Scheme 31) [155].…”
Section: Scheme 29 Wittig Reaction-cyanosilylationmentioning
confidence: 99%
“…In our previous study we reinvestigated the HWE/Michael addition combination by enlarging the scope of this powerful sequence to aqueous and solvent free conditions and from native sugars [10]. We demonstrated that C-glycoside amphiphiles are accessible from this methodology when Scheme 1 HWE/Michael addition sequence for the preparation of C-pyranosides and/or C-furanosides.…”
Section: Introductionmentioning
confidence: 95%
“…Solvent-free HWE reaction followed by a simple aqueous basic treatment yielded pure -C-glycosidic ketones with various alkyl chain lengths. In particular, C-glycosides derived from lactose, D-glucose and D-galactose possessing a short (C 7 ) alkyl chain 4-6 ( Figure 1) were obtained in moderate to good yields and high  selectivity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Examples for Wittig reactions with unprotected carbohydrates are summarized in reference [13][14][15][16][17][18][19][20][21][22][23], for reviews in this field see [24][25][26], whereas examples for Horner olefination (even in aqueous reaction medium) will be found in reference [27,28]. The reactions were carried out mostly at higher temperature.…”
mentioning
confidence: 99%